An African response to The postmodern Bible : is it helpful in breaking the stranglehold of idealist hermeneutics? - Chimeri, Dudzirah (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Phil.) -- University of Stellenbosch, 1998.